Facts about Potassium - R. Elaine Turner; Linda B. Bobroff (EDIS)
Potassium is a mineral found inside body cells. It is one of several minerals known as electrolytes. It is important because it helps regulate fluid and electrolyte balance, maintain normal blood pressure, transmit nerve impulses, control muscle contraction, and maintain healthy bones. Legumes are good sources of potassium, as are nuts and seeds. This 2-page fact sheet was written by R. Elaine Turner and Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, September 2014. (Photo: tofumax/iStock/Thinkstock.com)